GE_GERICHTE C/16130/2016 vom 12. Mai 2017 - GE Cour de justice (2017)
RAISON DE COMMERCE ; RADIATION DU RÔLE ; INTÉRÊT JURIDIQUEMENT PROTÉGÉ ; FRAIS JUDICIAIRES | CPC.242; CPC.106; CPC.107.1.e; CC.2.2; CPC.52;